The Drama of Space : Spatial Sequences and Compositions in Architecture. - Kleine, Holger (Walter de Gruyter GmbH, 2017)
"The experience of architectural spaces is formed by the way they are structured, arranged and orchestrated. The Drama of Space examines the composition and articulation of architectural spaces and presents a repertoire of means and strategies for shaping spatial experience. This fundamental approach to architectural design is presented in four parts - principles of spatial dramaturgy are traced from the study of three assembly buildings of the early modern age in Venice - theatre, film, music and theory provide insight into dramaturgical theory and practice - extensive visits to 18 international case studies offer new perspectives on contemporary architecture - the book ends with a systematic presentation of the dramaturgy of space and its means and parameters in architectural design"--Page 4 of cover